Combination of Organic Fertilizer and Biological Agent for Pest Control Spodoptera exigua of Plant Onion in Gending, Probolinggo - Agustini, Yusia; Purwatiningsih, P.; Sulistyanto, Didik (Jurnal ILMU DASAR, 2017)
Onion is one of lowland vegetables commodity that has been long cultivated intensively by farmers in Indonesia. Probolinggo is one of the regions which give considerable contribution of producing onion to the national needs. In an effort to increase production, onion farmers in Probolinggo mostly relies on external supply in the form of artificial chemicals (fertilizers and pesticides). However, the using of artificial chemicals can cause pollution and damage the environment. So that utilization of biological agents and organic fertilizers which are environmentally friendly can become other solutions to increase the yield of onion production. Based on this case, it is very important in efforts to increase production of onion by combining organic fertilizers to enrich the content of organic matter in the soil with biological agents in tackling pests attack. Based on the research results in application of combining organic fertilizers granules plus NEP and biological agents Heterorhabditis sp. in District Gending Probolinggo shows that : 1. reducing the population of pests Spodoptera exigua up to 72.260%. 2. improving onion plant growth more optimal. From the result, it shows that the combination of organic fertilizer granule plus biological agents and NEP Heterorhabditis sp. (P2A1) is more effective than the combination of the others. Keywords: onion, biological agents, spodoptera exigua